Potentialities and Margins for Improvement of the European AI Alliance, an Example of Participatory Democracy in the Field of AI at EU Level - Gabriele Rugani (Athena, 2023)
This contribution focuses on the dialogue with stakeholders in drafting EU acts in the field of AI, with particular reference to the so-called “European AI Alliance”, which can be defined as the best example of “participatory democracy in the field of AI on European level”. After understanding what the AI Alliance is and how it works, and after making some considerations on its nature, the paper focuses on its role in the context of the drafting of EU acts, such as the Ethics Guidelines for Trustworthy AI and the AI Act Proposal. In the end, it will be possible to make some conclusive remarks and to formulate some suggestions, concerning the future of the AI Alliance and the need to exploit and improve it also, and especially, after the (eventual) adoption of the AI Act and of the other legislative proposals currently under discussion.